2021
DOI: 10.15330/pcss.22.2.345-352
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of interaction of components in the SIO2-C system: improvement of technical silicon production technological process

Abstract: In order to identify ways to improve the technological process of smelting metallic (crystalline) silicon of technical purity, a thermodynamic analysis of the interaction of components in the SiO2-C system is carried out that reveals the main factor in obtaining high-quality technical silicon is the elimination of superposition of the silicon carbonization process that is possible by carrying out a two-stage carbothermal reduction reaction, in that firstly the incomplete reduction of silica (SiO2) by solid car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A review of the references mentioned above, on the one hand, and the results of our own theoretical and experimental work on the carbothermal reduction of metal oxides [23,35,36,37], on the other, show that for small-scale production of target alloys, it is more convenient to conduct reduction reactions in a specially modernized plasmachemical arc furnace-reactor, with the possibility of simultaneous supply of solid and gasphase carbonaceous reducing agents.…”
Section: Advanced Environmentally Friendly Recovery Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the references mentioned above, on the one hand, and the results of our own theoretical and experimental work on the carbothermal reduction of metal oxides [23,35,36,37], on the other, show that for small-scale production of target alloys, it is more convenient to conduct reduction reactions in a specially modernized plasmachemical arc furnace-reactor, with the possibility of simultaneous supply of solid and gasphase carbonaceous reducing agents.…”
Section: Advanced Environmentally Friendly Recovery Technologiesmentioning
confidence: 99%
“…A systematic examination of the options for accelerating the recovery process while minimizing the environmental impact revealed that the primary goal is to maximize the efficiency of the application of methane and the synthesis gas released when reacting with metal oxides that have a high potential for recovery under appropriate thermodynamic conditions. In this regard, the mentioned plasma-arc melting technology of special plasma-chemical arc furnace-reactors with one liquid-metal bottom electrode provides the possibility of reverse vertical supply of the mentioned gas reagents [37]. In addition, we added a special side tuyere directed to the high-temperature reaction zone, with the possibility of injection and diffusion of methane in the melt's oxide layer, for the implementation of gas-phase reduction processes in the reactor-furnace (active power 100 kVA).…”
Section: Rational Technical Solution To Improve the Recovery Processmentioning
confidence: 99%